2002
DOI: 10.1097/01.asn.0000033327.65390.ca
|View full text |Cite
|
Sign up to set email alerts
|

Abolition of Hypertension-Induced End-Organ Damage by Androgen Receptor Blockade in Transgenic Rats Harboring the Mouse Ren-2 Gene

Abstract: Abstract. A sexual dimorphism in hypertension has been observed in both human and laboratory animal studies. The mechanisms by which male sex hormones regulate cardiovascular homeostasis are still not yet fully understood and represent the subject of this study. The possible involvement of androgen receptors in the development of hypertension and end-organ damage in transgenic rats harboring the mouse Ren-2 renin gene [TGR(mREN2)27] was studied. Male TGR(mREN2)27 rats were treated with the androgen receptor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 45 publications
6
39
1
2
Order By: Relevance
“…31,32 An animal model of hypertension-induced end-organ damage showed significant attenuation of renal damage by androgen receptor blockade with flutamide. 33 In uninephrectomy models, male rats developed greater proteinuria and mesangial sclerosis than did female rats. 34 Testosterone seems to amplify compensatory glomerular and tubular growth, which may promote glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 An animal model of hypertension-induced end-organ damage showed significant attenuation of renal damage by androgen receptor blockade with flutamide. 33 In uninephrectomy models, male rats developed greater proteinuria and mesangial sclerosis than did female rats. 34 Testosterone seems to amplify compensatory glomerular and tubular growth, which may promote glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is known to downregulate both ACE and the AT 1 receptor, as well as increase the expression of the AT 2 receptor and ACE2, which may further attenuate the actions of the ACE-ANG II-AT 1 axis (3,10,17,27,33,56,59). In contrast, testosterone may increase ACE and the AT 1 receptor as well as angiotensinogen (9,27). To our knowledge, the current studies are the first to document the sex-based differential expression of both circulating and tissue ANG II and ANG-(1-7) in any hypertensive strain.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the cardioprotective effects of estrogen replacement in mRen (2).Lewis rats, an ANG IIdependent model of hypertension, are consistent with its actions to directly attenuate key components of the RAAS, including angiotensin-converting enzyme (ACE) and the AT 1 receptor (12,40,45), as well as the increase of competing components such as ACE2 and the ANG II type 2 (AT 2 ) receptor or influence other signaling pathways (nitric oxide and prostaglandins) that may converge on the RAAS (3,11,41,60,65). Androgens, however, may also have a significant effect on cardiovascular regulation to increase blood pressure and accelerate renal injury that is associated with alterations of the RAAS, including the increased expression of renin, angiotensinogen, and ACE (6,8,9,47). Furthermore, estrogen may exhibit additional effects on the RAAS, including the stimulation of renin and angiotensinogen that in some instances may promote an increase in blood pressure (12).…”
mentioning
confidence: 99%
“…For example, renin 2 was reported to be an androgen-responsive gene (66,67). Moreover, overexpression of murine renin 2 in rats resulted in testosteronedependent hypertension (68). Furthermore, the RAAS has been suggested to have a greater impact on blood pressure regulation in males than in females: knocking out the gene encoding ACE1 decreased blood pressure in male but not female mice (69), and in a large population study, genetic linkage of the ACE locus with hypertension was found in men but not in women (70).…”
Section: Figurementioning
confidence: 99%